State of governance of religious communities in former Yugoslavia and the developments of the Bahá’í Community and Jehovah’s Witnesses - Zibelnik Badii, Aleksandra (Poligrafi, 2025)
Yugoslavia officially recognized major religious communities, including the Roman Catholic and Orthodox Churches and the Islamic community, while aro-und fifty smaller, unrecognized groups also existed by the 1960s. This study exami-nes state laws and the development of two such communities – Jehovah’s Witnesses and the Bahá’í community. Despite a legal framework that guaranteed religious freedom, including the separation of church and state and protection from co-ercion, the reality was shaped by tensions between government policies and reli-gious groups. This analysis explores how national identity, legal compliance, and ideological alignment with the state influenced the treatment of smaller religious communities within Yugoslavia’s broader framework of religious freedom.
Keywords: acceptance; cerkev; church; communism; conversion; Jugoslavija; komunizem; konverzija; persecution; preganjanje; religious community; sprejemanje; verska skupnost; Yugoslavia